Frequencies and ethnic distribution of ABO and RhD blood groups in China: a population-based cross-sectional study - Min Liu; Jue Liu; Shikun Zhang; Qiaomei Wang; Haiping Shen; Yiping Zhang (BMJ Open)
Objectives ABO and RhD blood groups are key factors affecting blood transfusion safety. The distribution of ABO and RhD blood groups varies globally, but limited data exist for ethnic distributions of these blood groups in Asian populations. We aimed to evaluate the distribution of ABO and RhD blood groups among Chinese ethnic groups.Design A population-based cross-sectional study.Setting Data on ABO groups and ethnicities were obtained from the National Free Preconception Health Examination Project (NFPHEP) with participants from 220 counties of 31 provinces in ChinaParticipants There were 3 832 034 participants aged 21–49 years who took part in the NFPHEP from January 2010 to December 2012 and were included in this study.Outcome Measures The proportion of ABO and RhD blood groups among different ethnic groups was calculated.Results ABO and RhD blood distribution was significantly different among nine ethnic groups (P<0.001). Compared with other ethnic groups, the Yi group had more A phenotypes (34.0%), and the Manchu (33.7%) and Mongolian (33.3%) ethnic groups had more B phenotypes. The Zhuang group had the greatest proportion of O phenotypes (41.8%), followed by the Miao group (37.7%). AB phenotypes were more frequent in the Uygur ethnic group (10.6%) but lower in the Zhuang group (5.5%). Meanwhile, RhD negativity (RhD–) was greater in the Uygur group (3.3%) than in the Mongolian (0.3%) and Manchu ethnic groups (0.4%). O RhD– blood groups were more frequent in the Uygur group (0.8%) than in the other ethnic groups (0.1%–0.4%, P<0.001).Conclusion ABO and RhD blood phenotypes vary across different ethnic groups in China. The diversity in the distribution of the ABO and RhD blood groups in different ethnic groups should be considered when developing rational and evidence-based strategies for blood collection and management.